Pengembangan Media Pembelajaran Augmented Reality Pada Mata Pelajaran Seni Budaya Di Smk Pembangunan Cibadak - Fakhri Abdillah Zulkifly; Luthpi Saepuloh; Arif Yudianto (Peneliti.net, 2022)
Learning media is a tool for educators to make it easier to convey learning to students, both physical and non-physical. It can be said that learning media are all forms and types of tools to support teachers in delivering learning materials to students, both physical learning media, such as original and artificial teaching aids, as well as non-physical learning media, such as slide presentation media, audio visual , as well as 2D/3D animation. Learning media is part of the whole system and learning process. The application of good learning media by educators, as well as a communicative and attractive style of speech for students, can facilitate the process of delivering material from educators to students, so as to increase student learning motivation. The development of learning media at this time, especially in ICT-based learning media, for example learning media that applies three-dimensional technology, namely Augmented Reality (AR), in the subject of Cultural Arts. Augmented Reality or usually called AR, is one of the new technologies known to the public, AR is a concept of combining the virtual world with the real world to generate information from data taken from a system on a designated real object so that the boundary between the two becomes increasingly thin. Art is a work that is made or created with extraordinary skills so that it is something beautiful or beautiful. The need for art and culture is a higher human need among other needs. This study aims to produce a product in the form of 3D learning media using Augmented Reality technology. The type of research used is R&D research and development with reference to the ADDIE research and development model which consists of five stages. The data collection method used by the researcher is interviews with subject teachers, and through classroom observations to students. Meanwhile, the method of collecting data is through a media feasibility assessment questionnaire from material experts, media and design experts, and user assessments, namely students. The results showed that the material expert validation obtained a presentation of 92% in the very appropriate category. The results of the media expert validation obtained a presentation of 88% in the very feasible category and field trials by students obtained a score of 85% in the